AKLIMATISASI PANAS, DINGIN, DAN HIPOKSIA DALAM LATIHAN FISIK: TINJAUAN LITERATUR RESPONS FISIOLOGIS ATLET - Kayla Safira Liestyana; Ahmad Sahid Insyagi; Putra Arnanda Ade Kusvian (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Exposure to environmental stressors such as heat, cold, and hypoxia induces substantial physiological strain on the cardiovascular, thermoregulatory, and respiratory systems. Recent research has shifted from studying isolated stress responses to exploring cross-adaptation, a phenomenon in which adaptation to one stressor enhances tolerance to another. This review synthesizes empirical findings from key studies investigating cross-adaptation mechanisms, particularly between heat and hypoxia, and their implications for athletic performance. Evidence from Gibson et al. (2017) and Willmott et al. (2024) demonstrates that heat acclimation improves hematological stability, increases plasma volume, enhances oxygen saturation, lowers heart rate, and reduces core and skin temperatures during exercise in hypoxic environments. Conversely, hypoxia acclimation has shown potential benefits for both normothermic and heat conditions, although performance effects remain inconsistent. Mechanistic insights indicate that thermoregulatory adjustments—such as earlier sweating onset and increased skin blood flow—play an important role in supporting physiological stability during combined heat and hypoxia exposure. These interactions hold practical relevance for athletes and physically demanding occupations with limited access to prolonged altitude training. This integrative review aims to compile physiological mechanisms, performance outcomes, and practical applications of cross-adaptation to evaluate its viability as an alternative or complementary strategy for preparing individuals for extreme environmental conditions.